2012
DOI: 10.1103/physreva.86.042701
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of cross sections forK-shell ionization by electron impact for C, O, Al, Si, and Ti

Abstract: Cross sections for K-shell ionization by electron impact were determined from films of Al, Si, and Ti and their oxides deposited on carbon substrates, for incident energies between 2.5 and 25 keV. The spectral processing of the x-ray emission spectra took into account corrections due to the presence of a spontaneous oxide layer formed on the monoelemental films and to the supporting material. Carbon K-shell ionization cross sections were determined from the contribution of the substrate to the measured spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
6
21
0
Order By: Relevance
“…5 for the oxygen isoelectronic sequence. A comparison of some K-shell measurements compiled by Llovet et al (2014), for example for C i, Al i, and Ti i (Limandri et al 2012), demonstrated a good agreement with the maximum difference between the measurements and the calculations with (11) at the peak for Ti i of less than 15%.…”
Section: Di: 1s Cross-sectionssupporting
confidence: 55%
“…5 for the oxygen isoelectronic sequence. A comparison of some K-shell measurements compiled by Llovet et al (2014), for example for C i, Al i, and Ti i (Limandri et al 2012), demonstrated a good agreement with the maximum difference between the measurements and the calculations with (11) at the peak for Ti i of less than 15%.…”
Section: Di: 1s Cross-sectionssupporting
confidence: 55%
“…It can be seen that there is a good agreement between the x-ray production cross section values obtained here and the other experimental results, particularly with those from Ref. [1]. The differences between the present data and those from [35] could be due to the fact that their results were obtained using an EDS instead of a WDS.…”
Section: Fig 3 Silicon K-shellsupporting
confidence: 86%
“…x-ray production cross section for single ionization. Black dots: present results; white dots: Zhu et al [35]; gray dots: Limandri et al [1] Figure 3 displays the results obtained for K-shell single ionization, along with data obtained by means of the bulk sample method [35] and through measurements performed irradiating a thin target [1]. It can be seen that there is a good agreement between the x-ray production cross section values obtained here and the other experimental results, particularly with those from Ref.…”
Section: Fig 3 Silicon K-shellsupporting
confidence: 78%
See 2 more Smart Citations